Fire and ice - Farshtey, Greg.; Farshtey, Greg.; Farshtey, Greg.; Farshtey, Greg.; Ameet Studio (Firm) (New York : Scholastic, 2014)
"Chima is under siege! The ice-wielding Hunters have awoken from their centuries-long sleep, and now they're freezing everything in their path--including the members of Chima's animal tribes! Laval and his friends must master the power of Fire CHI in order to save their home. But the secret to finding the Fire CHI and battling these frosty new enemies will take everything the heroes have got. And if they fail, Chima will be put on ice...permanently!"--Back cover.
Chima-- on ice! - The Hunters - Sir Fangar - Dreams about fire - The Phoenix City - Fire CHI - The long climb - Fear of fire - Operation nap time.
"Three stories in one!"
4-8
720
Accelerated Reader AR
Keywords: Animals -- Fiction; Adventure fiction -- Fiction; LEGO toys -- Fiction